HUBUNGAN TINGKAT PENGETAHUAN KEPALA KELUARGA DENGAN PEMBERIAN DIET PADA LANSIA YANG MENGIDAP HIPERTENSI DI RW 1 DUSUN DEMANGAN SELOMARTANI - Antok Nurwidi Antara; Susi Damayanti; Wa Ode Julianti Musrif (STIKES Wira Husada Yogyakarta, 2017)
BACKGROUND: World Health Organizarion - Community Study of the Eldelry Central Java found that hypertension and cardiovascular disease is the second largest disease suffered by the elderly after the arthritis that is equal to 15.2% of 1,203 cases. Approximately 60% of all premature deaths caused by patients suffering from mild hypertension (Fisher & Gordon 2005). According to the Central Statistics Agency (BPS) in 2010 life expectancy (UHH) population in Sleman district reached 75.1 years, while life expectancy at the level of Yogyakarta Province is 73.2 years. The number of pre-elderly population (45-59 years) are 53 146 people and the elderly (> 60 years) are 55 967 people, of total population are 1,090,567 people. The elderly population need serious attention in the health sector in order not to burden with preventive promotive programs (Dinkes Sleman, 2012). RESEARCH OBJECTIVES: To identify the relations between knowledge level from the head of the family with giving diet to elderly that have hypertension in rw 1 Dusun Demangan SelomartaniMETHODS: This study is a quantitative research using cross sectional approach. This is an analytic observational study conducted and observed at a time. The population in this study were families living in RW 1 Dusun Demangan that are 32 heads of family. Data were analyzed using Chi-Square. The study was conducted in June-July, 2016.RESULTS: There is a relations between knowledge level from family heads with giving Diet to elderly that Suffering from Hypertension in RW 1 Dusun Demangan Selomartani, with the value of the results showed significancy (p = 0.001 <0.05). Knowledge level of Head of the Family of the Elderly Suffering from Hypertension in Dusun Demangan, mostly categorized as good, there are 18 respondents (56.3%). Giving the Diet in the Elderly Suffering from Hypertension, mostly categorized is good, 20 respondents (62.5%).